STRESS AND COPING WITH STRESS: A REVIEW - Khawaja, Mohammad Younas; Yousafzai, Aziz ur Rehman (Journal of Ayub Medical College Abbottabad, 2004)
In medical parlance 'stress' is defined as a perturbation of the body's homeostasis. This demand on mind-body occurs when it tries to cope with incessant changes in life. Stress is a concept invented in the 1930s by Dr. Hans Selye.1 Dr. Selye admitted that stress is an abstract concept, and he admitted that stress has never been adequately defined. Dr. Selye's own definition of stress is the non-specific response of the body to any demand.